Traditional Herbal Medicine: A Potential Therapeutic Approach for Adjuvant Treatment of Non-small Cell Lung Cancer in the Future. (December 2022) - Huang, Jie; Li, Jia-Xin; Ma, Lin-Rui; Xu, Dong-Han; Wang, Peng; Li, Li-Qi; Yu, Li-Li; Li, Yu; Li, Run-Ze; Zhang, Hao; Zheng, Yu-Hong; Tang, Ling; et al.
Lung carcinoma is the primary reason for cancer-associated mortality, and it exhibits the highest mortality and incidence in developed and developing countries. Non-small cell lung cancer (NSCLC) and SCLC are the 2 main types of lung cancer, with NSCLC contributing to 85% of all lung carcinoma cases. Conventional treatment mainly involves surgery, chemoradiotherapy, and immunotherapy, but has a dismal prognosis for many patients. Therefore, identifying an effective adjuvant therapy is urgent. Historically, traditional herbal medicine has been an essential part of complementary and alternative medicine, due to its numerous targets, few side effects and substantial therapeutic benefits. In China and other East Asian countries, traditional herbal medicine is increasingly popular, and is highly accepted by patients as a clinical adjuvant therapy. Numerous studies have reported that herbal extracts and prescription medications are effective at combating tumors. It emphasizes that, by mainly regulating the P13K/AKT signaling pathway, the Wnt signaling pathway, and the NF-κB signaling pathway, herbal medicine induces apoptosis and inhibits the proliferation and migration of tumor cells. The present review discusses the anti-NSCLC mechanisms of herbal medicines and provides options for future adjuvant therapy in patients with NSCLC.